DIALOGIC PARADIGM OF COLLECTIVITY IN THE ORTHODOX TRADITION - Іщук, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the dialogic principles of the Orthodox models of collectivity through the analysis of their dogmatic and intellectual components. The central place of the conciliar model, as the desired communication ideal and their joint life is substantiated. Such attributive characteristics of the Orthodox collectivity as the need for subordination of an individual and society to the values ​​based on love for God, ecliziological, personalistic, and intersubjective components are singled out. The manifestation of these attributes in religious-philosophical collectivity concepts of N. Berdyaev, V. Lossky, and V. Soloviev has been considered in the article.